2017
DOI: 10.1186/s12903-017-0381-6
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of platelet rich plasma (PRP) on human gingival fibroblast, osteoblast and periodontal ligament cell behaviour

Abstract: BackgroundThe use of platelet rich plasma (PRP, GLO) has been used as an adjunct to various regenerative dental procedures. The aim of the present study was to characterize the influence of PRP on human gingival fibroblasts, periodontal ligament (PDL) cells and osteoblast cell behavior in vitro.MethodsHuman gingival fibroblasts, PDL cells and osteoblasts were cultured with conditioned media from PRP and investigated for cell migration, proliferation and collagen1 (COL1) immunostaining. Furthermore, gingival fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 61 publications
(42 reference statements)
1
26
0
1
Order By: Relevance
“…This high concentration of Sr was selected to be comparable to that reported as possible in an actual in vivo system regarding local delivery of Sr. 10 A few other substances have been found to achieve similar results, mostly platelet-derived growth factor (PDGF), platelet-rich plasma (PRP), and BMPs. [27][28][29] On the other hand, such substances have also been associated with some disadvantages such as high costs, high supra-physiological doses of growth factors, as well as unwanted side effects associated with recombinant therapies. 30 Studies reporting on possible side effects of Sr administration (local and systemic) have no findings which would support such deleterious effects.…”
Section: As a Result The Differentiation Of Pdlcs Into Osteoblast-limentioning
confidence: 99%
“…This high concentration of Sr was selected to be comparable to that reported as possible in an actual in vivo system regarding local delivery of Sr. 10 A few other substances have been found to achieve similar results, mostly platelet-derived growth factor (PDGF), platelet-rich plasma (PRP), and BMPs. [27][28][29] On the other hand, such substances have also been associated with some disadvantages such as high costs, high supra-physiological doses of growth factors, as well as unwanted side effects associated with recombinant therapies. 30 Studies reporting on possible side effects of Sr administration (local and systemic) have no findings which would support such deleterious effects.…”
Section: As a Result The Differentiation Of Pdlcs Into Osteoblast-limentioning
confidence: 99%
“…Most of the studies investigating the effect of hemoderivatives on cell behaviour have used a 20% concentration of the exudates for technical reasons (availability and quantity of blood, etc.) or to allow for comparison to the established literature [6,7,41,42]. Ultimately, an ideal in vitro or in vivo concentration has yet to be defined, and the result of this study was able to provide a unique insight into the effect that various concentrations common hemoderivative preparations have on cell function.…”
Section: Discussionmentioning
confidence: 99%
“…As autologous formulations, prepared via relatively simple chairside fabrication, these blood products have recently generated considerable interest in clinical regenerative medicine [2][3][4][5]. Growth factors, such as insulin-like growth factor-1 (IGF-I), platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), epidermal growth factor (EGF), platelet-derived epidermal growth factor (PDEGF) and fibrin matrix proteins, are found in these preparations at a higher concentration than in blood, and have been proposed to directly contribute to accelerating tissue regeneration [5][6][7]. Hemoderivative preparations have also been frequently used as a surgical adjuvant to improve healing and promote tissue regeneration in the treatment of intrabony defects [8][9][10], alveolar ridge augmentation [11], post-extraction socket preservation [12], treatment of membrane perforation [13] and maxillary sinus augmentation [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial PRP (GLO-PRP) has been used as complement to several regenerative dental techniques. Kobayashi et al [55] studied PRP characterization in vitro and its effect on PDL (periodontal ligament) cells, human gingival fibroblasts and osteoblast cell behavior. The outcomes have demonstrated that PRP induced proliferation, gingival fibroblast migration and expression of mRNA pro-wound healing molecules.…”
Section: Cells Culturesmentioning
confidence: 99%